PEMANFAATAN YOGHURT UBI JALAR UNGU (Ipomoea batatas Lamb.) â YUJU â UNTUK PERBAIKAN KADAR TRIGLISERIDA DAN KOLESTEROL TOTAL PADA TIKUS Sprague Dawley YANG DIBERI DIET TINGGI LEMAK - , QISTHIRA SWASTI AMIRINA, Dr. Ir. Nurliyani, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
year to year is increasing. CHD initiated by an increase in blood total cholesterol and triglycerides level (hyperlipidemia). Utilization of locally-based functional foods as a preventive and curative alternatives need to be developed as a supportive therapy in addition to pharmacological therapy that is less comprehensive. Purple sweet potato yoghurt is one of the functional food containing lactic acid bacteria, anthocyanin, and dietary fibers that play a role in the improvement of total cholesterol and triglycerides. Research about the yoghurt, anthocyanins and purple sweet potato fiber has been done but in the form of purple sweet potato yoghurt products has not been done yet. Objective: To determine the effect of purple sweet potato yoghurt "YUJU" on levels of total cholesterol and triglycerides Sprague Dawley rats fed a high-fat diet. Method: The quasi experimental study with a pretest and posttest study design with control group design.There were 30 Sprague Dawley male rats aged 2 months were divided into 5 groups, there were: KON (aquadest), YJ2 (YUJU 2ml), YJ4 (YUJU 4ml), SVT (simvastatin 0.8 mg), YJ4 + SVT (YUJU 4ml+simvastatin). Then continued with the intervention for 4 weeks. Analysis of total cholesterol and triglycerides made in the last week of high-fat feeding (pretest), 2 weeks after be given by the intervention (midtest) and end of the intervention (posttest). Data were analyzed using ANOVA and Kruskal Wallis (non-parametric test) to determine whether there were significant differences between treatment groups. Results: There were no significant differences in total cholesterol and triglycerides between treatment groups after the intervention, but there is a decreasing trend in each treatment group. Conclusions: Purple sweet potato yoghurt " YUJU " can not lower total cholesterol and triglyceride serum Sprague Dawley rats fed a high-fat diet. However, there was a decrease in total cholesterol and triglycerides from pretest to posttest.